(untitled) (Journal of Social Sciences Review, 2024)
This research explores the effects of social class and cultural background on the experiences of English as a Foreign Language learners at FATA University in Pakistan who have gone through intensive motivational states i.e. Directed Motivational Currents (DMCs). It addresses a crucial gap in the literature concerning the relationship between sociocultural variables and DMCs. The research on DMCs has not considered the significant effect that motivational intensity might have when a students are from different cultures and social backgrounds. The researchers particularly wanted to know what effects? If any? the different pathways leading to DMCs might have when the sociocultural background of the learner is diverse and different from that of learners in predominantly Western cultures. The researcher employed a qualitative research design with semi-structured interviews conducted with 25 undergraduate EFL students from various tribal backgrounds. The students who were interviewed for this research are in the pathway to differing futures. They opened the door to a discussion about the different expressions of motivation that they experience in light of their diverse tribal cultures. They offered distinct and sometimes overlapping perspectives about the energy for their DMCs.